Dinamika Perkembangan Industri Besar Di China Tahun 1998-2012 - Wijayanto, Muhammad Abipragolo, Dr. H. Kuswaji Dwi Priyono, M.Si, Drs. H. Muhammad Musiyam, M.T.P (2015)
This aimed studies was determined the growth level of large industries in China (since economic/financial crisis 1997) along 1998-2012-observed by three indicators: number of enterprises, the amount of labors and value added-and also analyzed its' spatial concentration pattern by using analytical descriptive method. The kinds of large industries in this studies including: (1) mining; (2) manufacturing; and (3) production and distribution of electricity, gas and water. The focused study was 31 provinces in China (Taiwan, Hong Kong and Macau excluded); as the unit of analysis was province. Secondary data obtained from any documents and literature, including the official website of China National Bureau of Statistics 2013. Data was analyzed by using analytical quantitative approach where spatial concentration of large industries was calculating by Gini Index, plotting into the Lorenz curve; afterwards mapping by each province based on Gini Index classifying and analyzing by regional complex approach. The results showed that, firstly, in 1998 China was not able to rise from financial crisis that hit most Asian countries, but later in the end of 2012, the industrial sector coming increased gradually-although in certain years were decline. The Government of China succeed to run industrial policies. Secondly, the spatial concentration pattern of Chinese large industries showed an average of 0.52 on Gini Index which means there were a high concentration of large industries in each province; where Zhejiang, Jiangsu, Guangdong and Shandong were always the highest industrial concentration. Regarding its location, the provinces were be in the eastern part of China, located in the coastal which has great potential as harbour closely linked to the global trading system.